2004
DOI: 10.1038/sj.cr.7290240
|View full text |Cite
|
Sign up to set email alerts
|

The spike protein of severe acute respiratory syndrome (SARS) is cleaved in virus infected Vero-E6 cells

Abstract: Spike protein is one of the major structural proteins of severe acute respiratory syndrome-coronavirus. It is essential for the interaction of the virons with host cell receptors and subsequent fusion of the viral envelop with host cell membrane to allow infection. Some spike proteins of coronavirus, such as MHV, HCoV-OC43, AIBV and BcoV, are proteolytically cleaved into two subunits, S1 and S2. In contrast, TGV, FIPV and HCoV-229E are not. Many studies have shown that the cleavage of spike protein seriously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 20 publications
6
45
2
2
Order By: Relevance
“…Although other investigators reported the lack of proS processing [27][28][29][30], this report and others [31,32] detected CTFs by transient transfection of recombinant spike glycoprotein. Although other investigators reported the lack of proS processing [27][28][29][30], this report and others [31,32] detected CTFs by transient transfection of recombinant spike glycoprotein.…”
Section: Discussioncontrasting
confidence: 56%
“…Although other investigators reported the lack of proS processing [27][28][29][30], this report and others [31,32] detected CTFs by transient transfection of recombinant spike glycoprotein. Although other investigators reported the lack of proS processing [27][28][29][30], this report and others [31,32] detected CTFs by transient transfection of recombinant spike glycoprotein.…”
Section: Discussioncontrasting
confidence: 56%
“…Nevertheless, a recent study detected a cleaved S2 fragment in the lysate of cells infected with SARS-CoV, suggesting proteolytic processing of S protein of SARS-CoV in host cells. The proposed cleavage site in SARS-CoV (RS 667-668 ) also is found in bat-SARS-CoV (RS 653-654 ) (27). Further studies are required to determine whether the S protein of bat-SARSCoV also is cleaved into S1 and S2 subunits.…”
Section: Wild Animal Surveillance Identification Of Bat-sars-cov Anmentioning
confidence: 99%
“…As a new member of the coronavirus family, SARS-CoV shares with other coronaviruses some similarity and common features in the amino acid sequences of the S protein [8]. It has been found that the S protein of SARS-CoV is posttranslationally cleaved into S1 and S2 functional domains in the process of viral infection [9]. However, the impact of this cleavage on viral infectivity remains unclear [10].…”
Section: Sars-cov; Spike Protein; Protease Factor Xa; Protease Inhibimentioning
confidence: 99%